IMPLEMENTASI DAKWAH MENGGUNAKAN KONSEP KITAB WISHAYA AL ABA LI AL-ABNA PADA PERILAKU PACARAN REMAJA (STUDI MENINGKATKAN NILAI SPIRITUAL REMAJA) - Widyanto Triatmojo (Program Studi Manajemen Dakwah, FUAD, IAIN Pontianak, 2021)
Adolescence is a period of transition from childhood to adulthood at the age of 10 years to 20 years. One of the tasks of adolescent development is attraction to the opposite sex. Romantic relationships will also have a big influence on adolescents. In Indonesia, dating is defined as a process of introducing the period before marriage. Actually in Islam, sometimes dating is also known as the ta'aruf process. In the case of dating adolescents, the counselor should see that dating is a language and language is a culture that should be a forum for carrying out the dakwah process for adolescents. This article describes the concept of dating from 3 disciplines, namely psychology, culture and Islamic dakwah. This article uses the Islamic dakwah approach as an alternative solution to convey religious values ??to adolescents who are dating. Islamic dakwah, include Islamic concepts that aim to shape behavior in accordance with the orders of Allah SWT.